TINJAUAN TERHADAP MINAT MAHASISWA DALAM MEMILIH JURUSAN ADMINISTRASI BISNIS (Studi Kasus Jurusan Administrasi Bisnis Politeknik Negeri Sriwijaya) - Lisnini Lisnini; Abd Hamid; Miama LPN (Politeknik Negeri Sriwijaya, 2014)
The research is about how the collegian interest in choosing business Administration major. The respondents investigated in this research was the collegian of State Polytechnic of Sriwijaya majoring in Business Administration. To collect the data to find out collegian interest, the researcher used technique of questionnaire distribution. From the questionnaire researcher distributed, 113 respondents (60,43%) were agreed that choosing majoring Business Administration is basic of attitude of each collegian to that major and 122 respondents (65,24%) agreed that personality of someone have important role in choosing Business Administration major. Besides that 114 respondents (60,96%) agreed that culture of each collegian have important role too, and then 88 respondents (47,06%) agreed that social class is the basic for choosing Business Administration major. From that result, researcher could conclude that personality, attitude, culture, and then social class of collegian were the most strong basic in making collegian interest in choosing Business Administration major. Thus the researcher recommended that Business Administration major of State Polytechnic of Sriwijaya could increase quality of alumnus Business Administration major.